Tide gauge data for Tutakoke River stations, central Yukon-Kuskokwim Delta, 2007-2017 ... - Jorgenson, Mark Torre (NSF Arctic Data Center, 2025)
We maintained water-level recorders (Hobo Water Level recorders, U20-001-04, 0.5 to 1 hour intervals) at three stations (TG1, TG2, TG3) near Transect T5 (Fig. SI1) at the mouth of the Tutakoke River along the outer coast of the central portion of the Yukon-Kuskokwim Delta for various periods from 2007 to 2017. The loggers were installed in pipes buried in mud at the bottom of tidal guts to avoid ice scouring during winter; the installations were near the lower tidal range, but did not capture the full tidal range. Data field descriptions are provided in the metadata file. ...